Does the Gap Model Work in Asia? - McDermott, C.; Coe, David (Washington, D.C. : International Monetary Fund, 1996)
There is considerable evidence from industrial countries that the output gap is an important determinant of inflation. We examine whether the gap model also works in developing, newly industrializing, and industrial Asian economies. Our output gaps are based on a new nonparametric estimation procedure for trend output that does not require an arbitrary specification of the degree to which the data are smoothed. We test simple versions of the gap model in which the change in inflation is related to the output gap, as well as to the money supply and the terms of trade. We conclude that the gap model works very well in almost all of the Asian economies we study.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet